Receptor-interacting protein kinase 3 as a predictive adjuvant chemotherapy marker after lung adenocarcinoma resection - Chung, Jae Heun; Yoon, Seong Hoon; Kang, Yong Jung; Kim, Yun Seong; Son, Bong Soo; Kwon, Ryuk Jun; Han, Jun Hee; Kim, Do Hyung (Annals of Translational Medicine, 2019)
Background: This study assessed the predictive value of receptor-interacting protein kinase 3 (RIPK3) expression and its correlation with clinicopathological characteristics, disease-free survival, and overall survival of patients with cisplatin-based adjuvant chemotherapy after lung adenocarcinoma resection. Methods: This study included 50 patients who underwent cisplatin-based adjuvant chemotherapy after lung adenocarcinoma (stage IB–IIIA) resection. Immunohistochemical analysis was performed by probing tumor tissue microarrays with anti-RIPK3 antibody. Results: High RIPK3 expression was detected in 24 (48.0%) of the 50 patients. Moreover, high RIPK3 expression was associated with a prolonged disease-free survival (P=0.015) but not with a prolonged overall survival (P=0.109) of the patients who underwent cisplatin doublet therapy after lung adenocarcinoma resection. We also examined whether RIPK3 expression was associated with prognosis based on chemotherapeutic response and found that patients with low RIPK3 expression showed a higher tendency of developing a progressive disease [14/26 (53.8%) patients] than patients with high RIPK3 expression [6/24 (25.0%) patients] (P=0.03). Results of Cox univariate proportional hazards regression model showed that age, N stage, and high RIPK3 expression (P=0.04) were associated with the prolonged disease-free survival of the patients who underwent cisplatin-based adjuvant chemotherapy after lung adenocarcinoma resection. Conclusions: These results suggest that RIPK3 overexpression is a potential biomarker to identify patients with lung adenocarcinoma who can benefit the most from cisplatin-based adjuvant chemotherapy after complete adenocarcinoma resection.